Minimal-dose resistance training for improving muscle mass, strength, and function: a narrative review of current evidence and practical considerations - Fyfe, J. J.; Hamilton, D. L.; Daly, R. M. (Sports Medicine, 2022)
Resistance training (RT) is the only non-pharmacological intervention known to consistently improve, and therefore offset age-related declines in, skeletal muscle mass, strength, and power. RT is also associated with various health benefits that are underappreciated compared with the perceived benefits of aerobic-based exercise. For example, RT participation is associated with reduced all-cause and cancer-related mortality and reduced incidence of cardiovascular disease, hypertension, and symptoms of both anxiety and depression. Despite these benefits, participation in RT remains low, likely due to numerous factors including time constraints, a high-perceived difficulty, and limited access to facilities and equipment. Identification of RT strategies that limit barriers to participation may increase engagement in RT and subsequently improve population health outcomes. Across the lifespan, declines in strength and power occur up to eight times faster than the loss of muscle mass, and are more strongly associated with functional impairments and risks of morbidity and mortality. Strategies to maximise healthspan should therefore arguably focus more on improving or maintaining muscle strength and power than on increasing muscle mass per se. Accumulating evidence suggests that minimal doses of RT, characterised by lower session volumes than in traditional RT guidelines, together with either (1) higher training intensities/loads performed at lower frequencies (i.e. low-volume, high-load RT) or (2) lower training intensities/loads performed at higher frequencies and with minimal-to-no equipment (i.e. resistance `exercise snacking`), can improve strength and functional ability in younger and older adults. Such minimal-dose approaches to RT have the potential to minimise various barriers to participation, and may have positive implications for the feasibility and scalability of RT. In addition, brief but frequent minimal-dose RT approaches (i.e. resistance `exercise snacking`) may provide additional benefits for interrupting sedentary behaviour patterns associated with increased cardiometabolic risk. Compared to traditional approaches, minimal-dose RT may also limit negative affective responses, such as increased discomfort and lowered enjoyment, both of which are associated with higher training volumes and may negatively influence exercise adherence. A number of practical factors, including the selection of exercises that target major muscle groups and challenge both balance and the stabilising musculature, may influence the effectiveness of minimal-dose RT on outcomes such as improved independence and quality-of-life in older adults. This narrative review aims to summarise the evidence for minimal-dose RT as a strategy for preserving muscle strength and functional ability across the lifespan, and to discuss practical models and considerations for the application of minimal-dose RT approaches.